Save the Children’s Roles in Fulfilling Global Child Rights: Implementer, Catalyst, and Partnership - Gabriela Kilau Gemilang (Department of International Relations, Universitas Brawijaya, 2025)
ABSTRACT Save the Children, a major international non-governmental organization (INGO), in fulfilling global children's rights by applying David Lewis’s theoretical framework that categorizes INGOs as implementers, catalysts, and partners. This qualitative-descriptive study utilizes document analysis and literature review as its primary methodology. As an implementer, Save the Children delivers essential services in health, education, and emergency relief, including innovative programs to combat pneumonia and inclusive education models for marginalized children. As a catalyst, the organization drives policy reforms and advocates for the protection of children's rights globally through public campaigns and legislative engagement. As a partner, it establishes strategic collaborations with governments, international agencies, and local organizations to ensure program sustainability and inclusive participation. The findings demonstrate that Save the Children effectively integrates these three roles across multiple sectors to uphold child welfare and advance Sustainable Development Goal 4. Furthermore, this study highlights the organization’s capacity to navigate global-local dynamics and contribute to transnational development governance, positioning itself as a key actor in the international child rights regime. Keywords: INGO, Save the Children, child rights, global development, transnational actors